Funds Allocation Mapping And Corporate Social Responsibility Program (Program Kemitraan Dan Bina Lingkungan-Pkbl): Case In Indonesia (Global Journal of Management and Business Research, 2012)
A company should have a strong commitment in their PKBL implementation program. Results from several empirical studies concluded: companies that successfully implemented their PKBL programs tend to gain impacts for their financial and non-financial performance. Even though, there are still several companies that face hardships in implementing their PKBL programs. One of the main causes is the non-existence of data information system as the foundation for PKBL strategic planning. The aim of this study is to describe the mapping of funds allocation and PKBL program based on seven criteria: company reputation, conflict potency, income contribution, manpower absorption, business opportunity, region economy growth, and even distribution. The research type is census by case study in one BUMN (stated owned enterprise) in Indonesia. Research sample is 60 people consist of manager and PKBL executor. Statistic techniques used Analitycal Hierarchy Process (AHP). The result shows that seven criteria can be used as the foundation for the even distribution of funds allocation and PKBL program. This result supports the research conducted by Branco and Rodrigues (2006), Cerin (2002); Fombrun Shanley (1990), Juholin (2005); Silberhorn
Keywords: mapping; funds allocation; PKBL program; criteria of funds allocation